Extrato aquoso da Samanea tubulosa (Benth.) Barneby & Grimes na alimentação da tilápia-do-Nilo: efeitos sobre o crescimento, saúde e atividade antioxidante no tecido muscular - Garcêz, Kelli Flores (2021)
In intensive production systems, fish are exposed to stressful conditions, which can negatively interfere with their homeostasis. In this context, the use of natural additives in fish feed, such as Samanea tubulosa plant extract to overcome the negative effects of stress on fish growth and healt is interesting, due to its high antioxidant activity, low toxicity and biodegradation in the aquatic environment.This study evaluated the effects of dietary supplementation of S.tubulosa extract on Nile tilapia growth, health and antioxidant activity of muscle tissue. Fishes (starting weight 113.5 ± 9.0g) were randomly distributed in 12 circular tanks (250 L) and fed twice a day (09:00h and 16:00h) until apparent satiety for 60 days in a completely randomized design with three treatments (control; 2% and 4% dietary plant extract) (n=3). After feedind period, biometrical and biological data were collected to calculate growth performance, hematological analysis and antioxidant activity of muscle tissue. Results were evaluated for statistical assumptions of normality (Cramer Von Mises) and homoscedasticity (Brown-Forsythe) and submitted to ANOVA. Significant effects, were compared by the Tukey test (α=0.05). There was no significant effect on fish growth and hematology. Antioxidant activity in muscle tissue increased (p<0.05) in fish supplemented with 4% plant extract according to the ABTS method when using the QUENCHER procedure. After obtaining the methanolic extract from muscle tissue, fish fed with 4% plant extract supplementation also showed higher (p<0.05) antioxidant activity according to the FRAP method. However, it was observed no effect (p>0.05) on the lipidic oxidation process (TBARS) during seven days of muscle tissue evaluation. The inclusion of 4% dietary S.tubulosa plant extract increased antioxidant activity in fish muscle tissue despite not slowing down the lipidic oxidation processes. In addition, S. tubulosa dietary supplementation did not show toxicity to Nile tilapia.